Optimizing Finger Painting to Enhance Painting Skills in Early Childhood - Michala Michala; Ulfiyah Ulfiyah; Eti Juhaeti; Iis Dewi Hartati (Early Childhood Development Gazette, 2025)
This study aimed to improve the painting skills of children aged 5–6 years through finger painting activities at TK Alam Jabal Nur Gunung Jati Cirebon. The classroom action research was conducted in two cycles, consisting of planning, implementation, observation, and reflection stages. Data were collected through observation and assessment of children’s ability to draw various shapes and paint with diverse objects. The findings indicated a significant improvement from the pre-cycle, which showed a low interpretation, to the second cycle, which reached a high category. Children who were initially hesitant and afraid of making mistakes became more confident, willing to experiment, and able to combine colors and shapes more creatively. Providing examples of techniques and teacher demonstrations proved to be key factors of success, consistent with literature emphasizing the importance of guidance and creative exploration. These findings highlight that finger painting is an effective pedagogical strategy to foster fine motor skills, creativity, and self-expression in early childhood, while also contributing to innovative practices in early childhood art education.